1980
DOI: 10.3109/00365598009181197
|View full text |Cite
|
Sign up to set email alerts
|

The 125I-Hippuran Renogram in Rabbit Kidneys After Graded Warm Ischaemia

Abstract: 125I-Hippuran renography was performed after temporary renal arterial clamping in contralateral nephrectomized rabbits. Mean renograms for the experimenttal groups were calculated for 0, 1, 1 1/2, 2, 2 1/2 and 3 h of warm ischaemia. The appearance phase, the 1 min uptake phase and excretion ratio were evaluated. The kidney function was monitored by serum-creatinine. Warm ischaemia of 1, 1 1/2 and 2 h resulted in a late maximum peak and delayed excretion, and for the last group in an accumulation curve. The upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…[3] Several reports have suggested that the absence of perfusion or tracer uptake on renal scintigraphy correlates with conditions that confer a grave prognosis for survival of the renal transplant,[4] uptake of OIH is proportional to the renal viability and is well-correlated to the kidney's ability to regain normal function after ischemic damage, as demonstrated in an animal model. [7] Importantly, it takes only a few minutes after initiation of renal scintigraphy to obtain this critical information, allowing a prompt decision regarding further patient management. [8] Recent evidence indicates that transplant function in those patients can be saved by prompt restoration of blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Several reports have suggested that the absence of perfusion or tracer uptake on renal scintigraphy correlates with conditions that confer a grave prognosis for survival of the renal transplant,[4] uptake of OIH is proportional to the renal viability and is well-correlated to the kidney's ability to regain normal function after ischemic damage, as demonstrated in an animal model. [7] Importantly, it takes only a few minutes after initiation of renal scintigraphy to obtain this critical information, allowing a prompt decision regarding further patient management. [8] Recent evidence indicates that transplant function in those patients can be saved by prompt restoration of blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Άλλοι συγγραφείς αναφέρουν ότι σε κονίκλους με μονήρη νεφρό, ο οποίος όμως δεν έχει υποστεί μερική νεφρεκτομή, βιοχημικές διαταραχές ξεκινούν να εμφανίζονται μετά από 120 λεπτά θερμής ισχαιμίας (Dahlager et al, 1980). Είναι όμως γνωστό ότι η αφαίρεση νεφρικού παρεγχύματος, πέρα από στρεσσογόνος επέμβαση, επιβαρύνει αισθητά και την συνολική διηθητική ικανότητα του νεφρού .…”
Section: άθροισμα 4unclassified